The Transformation of Ecosufistic Values in Character Education at SMPIT Al Uswah Tuban: A Field Study Inspired by Jalaluddin Rumi’s Matsnawi - Muhammad Romadlon Habibullah; Hamidatun Nihayah; Ana Rahmawati; Moh shahid bin mohd saufi (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
This study aims to explore how ecosufistic values found in Matsnawi are transformed into character education practices at SMPIT Al Uswah Tuban. The study adopts a qualitative interpretive approach with a descriptive-exploratory design. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed thematically using an educational hermeneutic framework to interpret the school's implementation of ecosufistic values. Findings indicate that core ecosufistic principles such as harmony between humans and nature, ontological unity of all creation, and ecological balance are embedded within the school's spiritual routines, teacher modeling, and reflective learning processes. The use of Matsnawi’s narratives and symbols enhances students’ ecological awareness and fosters a spiritually grounded transformation of character. This study has an impact on the development of an Islamic character-education model based on ecosufism that is not only spiritually meaningful but also pedagogically relevant for addressing today’s ecological challenges. In addition, it provides practical contributions for curriculum developers, educators, and policymakers to integrate classical Islamic texts as a profound source of ecological ethics, thereby fostering sustainable ecological awareness among younger generations.Keywords: Ecosufism, Islamic Character Education, Matsnawi, Sufistic Pedagogy, Ecological Ethics, Spiritual Ecology